Potential of mushroom mycelia for sound absorption and thermal insulation in hot and humid climates - Jugkrapongthakul, Acomepuk; Sridaranon, Nattaree; Visitsak, Sopa (Agriculture and Natural Resources, 2025)
Importance of the work: Mycelium has demonstrated potential as a high-performance alternative to conventional insulation materials. However, it remains an emerging technology. This research focused on developing mycelium-based materials under minimal environmental controls outside the laboratory. Objectives: This research aims to explore the potential of developing sound-absorbing and heat-insulating materials from suitable mushroom mycelium species grown on agricultural waste, under minimum environmental controls, in Thailand’s hot and humid climate. Materials and Methods: Grey oyster mushroom [Pleurotus ostreatus (Jacq.ex Fr) Kummer] mycelium was cultivated in a box using different substrate mixing ratios of raw rice husks and rubberwood sawdust, under temperature and humidity controls ranging from 30ºC to 37ºC and 50% to 70%, respectively. The optimal substrate mixing ratio was then used to cultivate prototype materials for property testing in a laboratory. Results: The experimental results indicate that the optimal substrate composition for mycelium growth is a mixing ratio by weight of 2.5:0.1:0.5 (rubberwood sawdust:grey oyster mushroom mycelium:water). The square-shaped prototypes (size 10.50 × 10.50 cm, thickness 2.50 cm) exhibited an average density of 279.63±4.28 g/cm³, while the round-shaped prototypes (Ø13.00 cm, thickness 2.00 cm) exhibited an average density of 329.68±9.58 g/cm³. The developed prototypes comply with ASTM C423 standards (NRC > 0.40) and TIS 2303-2549 standards (thermal conductivity ≤ 0.066 W/mK). They displayed effective sound absorption performance within the frequency range of 1,000–5,000 Hz, with rough surfaces achieving a higher noise reduction coefficient (NRC = 0.43±0.03) compared to smooth surfaces (NRC = 0.41±0.022). The average thermal conductivity (k-value) was recorded as 0.065±0.001 W/mK. Additionally, the prototypes demonstrated fire-retardant properties, enhancing their safety profile for construction and insulation applications.